Staphylococcus lugdunensis in several niches of the normal skin flora - Bieber, L.; Kahlmeter, G. (Clinical microbiology and infection, 2010)
Staphylococcus lugdunensis is a coagulase-negative staphylococcus (CNS). Its pathogenicity and virulence are more similar to Staphylococcus aureus than to a CNS. It causes severe infections with high mortality, such as endocarditis, but more often painful and prolonged skin- and soft-tissue infections. Little is known of its normal habitat. Whether it is an integral part of the normal skin flora like many other CNS has been questioned, since it is rarely seen in blood cultures. This study was designed to determine whether S. lugdunensis has a niche in the normal skin flora and to compare S. lugdunensis and S. aureus in these niches. From 75 healthy subjects in Kronoberg County, Sweden, 525 swabs were obtained from the nose, axilla, perineum, groin, breast, toe and nail bed of the first toe. Significantly more of the 525 skin samples as well as of the 75 healthy subjects yielded S. lugdunensis (50/75) as opposed to S. aureus.(16/75). Swabs from the nose frequently yielded S. aureus, but only rarely S. lugdunensis. Swabs from the groin and the lower extremities, especially the nail bed of the first toe, often yielded S. lugdunensis but rarely S. aureus. This study shows that S. lugdunensis is an integral part of the normal skin flora, primarily of the lower abdomen and extremities, and that the niches of this coagulase-negative staphylococcus are distinctly different from those of S. aureus. The predominant niches of S. lugdunensis explain why the bacterium is an uncommon contaminant of blood cultures.